Prevalence of Anxiety and Depression in Medically Ill Patients Admitted In OPD of AIMS Muzaffarabad AJ&K: Prevalence of Anxiety and Depression - Manzoor, Sumera (Pakistan Journal of Health Sciences, 2023)
Neuropsychiatric disorders, particularly high levels of anxiety and depressive symptoms, are increasing in primary health care settings because of their impact on quality of life, service satisfaction, medication adherence, patient outcomes, and functioning increase. Objective: To assess the prevalence of anxiety and depression disorder in patients of medical OPD and investigates its prevalence with medical illnesses. To contribute in raising awareness about the significance of medical illnesses and its relation with anxiety and depression. Methods: Descriptive study design was used. The study analyzed 120 male and females. Hospital anxiety and depression Scale (HADS) was used to investigate the prevalence in medically unwell patients across all age and gender categories. The study took place in Muzaffarabad October 2020 to March 2021. Performa was circulated physical availability of participants. Convenient sampling technique was used for data collection. Patients with recognized psychiatric problems were not allowed to participate in trail. Analyze data with IBM SPSS (Statistical Package for the Social Sciences) version-21.0. Results: Overall 91% of patients showed depression and anxiety disorders of various severities. A significant inverse correlation is found between Anxiety and depression and medical illnesses of p-value of p 0.05 as per chi-square test. Conclusions: Finding suggests that medical illnesses may have positive influences on mental health disorder. The occurrence of co-morbidity between anxiety and depression and medical condition is common and remain undiagnosed, thus lowering depressive scores and enhancing mental health.